Smart Microgrids From Design to Laboratory-Scale Implementation - Bahrami, Shahab; Mohammadi, Ali (Springer International Publishing : Imprint: Springer, 2019)
In this book the authors first provide a comprehensive survey on the available studies on control, management, and optimization strategies in AC and DC microgrids. The authors then provide the design of a laboratory-scale microgrid system. Finally, a real-world implementation of the deigned framework is provided. This book paves the way for researchers working on the smart microgrids spread over the fields of electrical engineering, power systems, and smart infrastructures. Furthermore, it provides the readers with a comprehensive insight to understand an in-depth big picture of smart microgrids as well as an all-inclusive framework for laboratory-scale implementation of a microgrid. It is suitable for senior undergraduate students, graduate students who are interested in research in areas related to future smart grids and microgrids, and the researchers working in the related areas. This book also can be used as a reference book for researchers who want to develop laboratories on smart microgrids for future research.